Laser-based soldering of a high-resolution optical filter instrument for space applications - Hornaff, Marcel; Kepper, Mariia; Beckert, Erik; Prevost, Eddie; Toubhans, Isabelle; Descours, Francis; Eberhardt, Ramona; Tuennermann, Andreas (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
A laser based soldering technique - Solderjet Bumping - using liquid solder droplets in a flux-free process with localized thermal impact demonstrates the all inorganic, adhesive free attachment of optical components and support structures made of heterogeneous materials for a high-resolution optical filter under harsh environmental conditions. Space applications demand an attachment technology which maintains the precise alignment of bonded components and overcomes challenges of common adhesives such as being more radiation resistant and appropriate for vacuum environments. Besides, stress and strain induced into optical components can deteriorate the wavefront of passing light and therefore reduce the system performance significantly. The presented case study shows the mandatory changes in the design of an optical filter instrument according to the boundary conditions of Solderjet Bumping for different bonding issues. First, a filter window made of N-BK10, covering the optical sensor beneath, is soldered into a frame of DilverP1®. Second, this sub-assembly is aligned w.r.t. to fiducials on a support structure and is attached in this state by soldering as well. The process chain of Solderjet Bumping including cleaning, wettable metallization layer, handling, soldering and inspection is discussed. This multi-material approach requires well-defined reflow energies to melt the spherical shaped solder preforms to create a media-fit joint and to prevent damages on the fragile filter window simultaneously. The findings of process parametrization and environmental testing are presented. The optical performance with respect to stress/strain before and after soldering as well as the alignment state are evaluated using non-contact optical techniques.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Earth observation; Laser based soldering; Optical filter assembly; Solderjet Bumping